Design and analysis of sugarcane breeding experiments: a case study - Santos, Alessandra dos (2017)
One purpose of breeding programs is the selection of the better test lines. The accuracy of selection can be improved by using optimal design and using models that fit the data well. Finding this is not easy, especially in large experiments which assess more than one hundred lines without the possibility of replication due to the limited material, area and high costs. Thus, the large number of parameters in the complex variance structure that needs to be fitted relies on the limited number of replicated check varieties. The main objectives of this thesis were to model 21 trials of sugarcane provided by \"Centro de Tecnologia Canavieira\" (CTC - Brazilian company of sugarcane) and to evaluate the design employed, which uses a large number of unreplicated test lines (new varieties) and systematic replicated check (commercial) lines. The mixed linear model was used to identify the three major components of spatial variation in the plot errors and the competition effects at the genetic and residual levels. The test lines were assumed as random effects and check lines as fixed, because they came from different processes. The single and joint analyses were developed because the trials could be grouped into two types: (i) one longitudinal data set (two cuts) and (ii) five regional groups of experiment (each group was a region which had three sites). In a study of alternative designs, a fixed size trial was assumed to evaluate the efficiency of the type of unreplicated design employed in these 21 trials comparing to spatially optimized unreplicated and p-rep designs with checks and a spatially optimized p-rep design. To investigate models and design there were four simulation studies to assess mainly the i) fitted model, under conditions of competition effects at the genetic level, ii) accuracy of estimation in the separate versus joint analysis; iii) relation between the sugarcane lodging and the negative residual correlation, and iv) design efficiency. To conclude, the main information obtained from the simulation studies was: the convergence number of the algorithm model analyzed; the variance parameter estimates; the correlations between the direct genetic EBLUPs and the true direct genetic effects; the assertiveness of selection or the average similarity, where similarity was measured as the percentage of the 30 test lines with the highest direct genetic EBLUPs that are in the true 30 best test lines (generated); and the heritability estimates or the genetic gain.